Analisis Hukum Gay-Lussac Tentang Fluida Pada Kaleng Parfum (Dalam Kajian Studi Literatur) - I Ketut Mahardika; Singgih Bektiarso; Hita Mara Cecilia; Ira Wanda Rahyuni Pitri; Berlian Marsha Malihah; Mafaza Nuris Sabeta (Jurnal Ilmiah Wahana Pendidikan, 2023)
We often know that when reading perfume products made from cans at the bottom there is a warning that is to keep it below 15ºC-21ºC stating that perfume cans should not be at high temperatures because it will cause the cans to explode caused by the expansion of the gas inside. in a perfume can. Based on a study of Gay-Lussac's law observed by Joseph Louis Gay-Lussac which relates to pressure, volume and temperature of a gas. This law was created when Joseph Louis Gay Lussac boarded a hot air balloon and produced a formula that reads "a gas will experience an increase in pressure at a certain mass if it experiences a temperature increase in a constant volume". The relationship between pressure and temperature influences each other, namely when the temperature is high it will produce high pressure, conversely when the temperature is low then the pressure produced will decrease, but the conditions must be in a constant volume. Then the result of the graph compared to temperature will be directly proportional to the pressure. Thus, it is closely related to the creation of explosions that occur in perfume cans when the temperature is > 21°C . We conducted this research to prove that temperature affects the expansion of gas in perfume cans by applying the method of literature study by collecting some of the research results that have been done.